1985
DOI: 10.1007/bf01997523
|View full text |Cite
|
Sign up to set email alerts
|

Recovery following experimental harvesting ofLaminaria longicruris andL. digitata in southwestern Nova Scotia

Abstract: Laminaria population variables and understory community composition were monitored just prior to, and for two summers following, a September 1980 experimental total harvest of L. longicruris De la Pylaie and L. digitata (L.) Lamouroux within two plots in Lobster Bay, Nova Scotia. Both plots, distinguished mainly by depth, were characterized by high Laminaria standing crop and no recent history of extensive sea urchin grazing. Within the shallower plot (2-3 m below MSL), recovery could not be assessed thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…This feature may explain some of the year-to-year variation in standing crop for unharvested populations of L. longicruris and L. digitata (Table 1). The location of this study is subject to storms and ice scouring during winter causing plant mortahties (Smith 1985). This study predicts increased success of L. longicruris following a disturbance because of reduced standing crop and plant densities, as observed for Lessonia nigrescen.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This feature may explain some of the year-to-year variation in standing crop for unharvested populations of L. longicruris and L. digitata (Table 1). The location of this study is subject to storms and ice scouring during winter causing plant mortahties (Smith 1985). This study predicts increased success of L. longicruris following a disturbance because of reduced standing crop and plant densities, as observed for Lessonia nigrescen.…”
Section: Discussionmentioning
confidence: 72%
“…Alternatively, canopy removal has also resulted in patterns of succession that do not immediately result in increased recruitment by the species removed , Santelices & Ojeda 1984a, and papers cited therein). This does not appear to be the pattern for this system (Smith 1985).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although Parke (1948) and Reynolds (1974) have reported life-spans of up to 3 yr in individuals, Parke (1948) demonstrated that the average life expectancy for L. saccharina in Great Britain was 2 yr. Chapman (1984) and Smith (1985) reported that the longevity of L. longicruris in Nova Scotia, Canada, was 25 and 20 mo, respectively. Populations of L. saccharina from LIS (Brinkhuis et al 1983) and intertidal populations of the same species from British Columbia, Canada, (Druehl & Hsiao 1977) were described as being annuals.…”
Section: Discussionmentioning
confidence: 99%